2016
DOI: 10.1124/jpet.115.230516
|View full text |Cite
|
Sign up to set email alerts
|

An Important Role for N-Acylethanolamine Acid Amidase in the Complete Freunds Adjuvant Rat Model of Arthritis

Abstract: The endogenous lipid amides, palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), exert marked antinociceptive and anti-inflammatory effects in animal models by engaging nuclear peroxisome proliferator-activated receptor-a. PEA and OEA are produced by macrophages and other host-defense cells and are deactivated by the cysteine amidase, N-acylethanolamine acid amidase (NAAA), which is highly expressed in macrophages and B-lymphocytes. In the present study, we examined whether a) NAAA might be involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 38 publications
(58 reference statements)
1
32
0
Order By: Relevance
“…As previously shown with other inflammatory stimuli, such as carrageenan (Solorzano et al, 2009), lipopolysaccharide (Ribeiro et al, 2015), and complete Freund's adjuvant (Bonezzi et al, 2016), local application of DNFB decreased PEA content in mouse ear tissue (Figure 3a) (P < 0.001, n ¼ 9). By contrast, no change was observed in the levels of oleoylethanolamide (OEA), another lipid amide agonist of PPAR-a ( Figure 3b) (Fu et al, 2003).…”
Section: Acute Topical Treatment With Arn077 Normalizes Pea Signalingsupporting
confidence: 78%
See 2 more Smart Citations
“…As previously shown with other inflammatory stimuli, such as carrageenan (Solorzano et al, 2009), lipopolysaccharide (Ribeiro et al, 2015), and complete Freund's adjuvant (Bonezzi et al, 2016), local application of DNFB decreased PEA content in mouse ear tissue (Figure 3a) (P < 0.001, n ¼ 9). By contrast, no change was observed in the levels of oleoylethanolamide (OEA), another lipid amide agonist of PPAR-a ( Figure 3b) (Fu et al, 2003).…”
Section: Acute Topical Treatment With Arn077 Normalizes Pea Signalingsupporting
confidence: 78%
“…Despite their rapid clearance, (S)-OOPP and ARN077 have been shown to suppress macrophage activation in vitro and to attenuate local inflammatory and nociceptive responses in vivo (Sasso et al, 2013b; Solorzano et al, 2009). NAAA inhibitors with greater metabolic stability, such as the b-lactam ARN726 and isothiocyanate AM9053, display significant anti-inflammatory activity after systemic administration in mouse models of lung (Ribeiro et al, 2015), joint (Bonezzi et al, 2016), and colon inflammation (Alhouayek et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAEs are primarily inactivated by hydrolysis to ethanolamine and fatty acid (8,9) carried out by two enzymes: fatty acid amide hydrolase (FAAH) (10) and N-acylethanolamine acid amidase (NAAA) (9). FAAH is widely distributed (11) although it is most abundant in the brain and liver (12), whereas NAAA is almost exclusively expressed in immune cells (13,14) such as monocytes and tissue macrophages (15,16) but is also found in prostate epithelium (13,17). In light of the analgesic and antiinflammatory actions of PEA, multiple NAAA inhibitors have been developed over the last decade (18,19) and shown to exhibit beneficial effects in a range of rodent models of human disease, including inflammation (20)(21)(22)(23)(24)(25), allergic contact dermatitis (26), spinal cord trauma (27), neuropathic pain (28,29), chronic pain (30), inflammatory bowel disease (31), lung inflammation (25,32), arthritis (14), and multiple sclerosis (33).…”
mentioning
confidence: 99%
“…We found that mRNA levels of NAAA, the specific hydrolase of PEA, remained constant during 10 days after SD. NAAA is almost exclusively expressed in immune cells (Bonezzi et al, 2016;Bottemanne et al, 2018) and is catalytically active at the acidic pH present during inflammation. In the SDE mouse model, no obvious inflammatory cell infiltration was found in ocular surfaces or LGs, which might explain why NAAA enzyme was not highly expressed.…”
Section: Discussionmentioning
confidence: 99%